(untitled) (Journal of Bangladesh Academy of Sciences, 2023)
Wave Energy is a type of renewable energy that uses the power of waves to generate electricity, and it is the largest estimated global resource form of ocean energy. This study deals with various techniques of wave power and focuses on the present scenario in the world and its potentiality in Bangladesh. The analysis of parameters of wave height, wavelength, and wave period; indicates the bright prospects of wave power in Bangladesh. J. Bangladesh Acad. Sci. 47(1); 21-25: June 2023